"But basically you're feeling well, are you?": tag questions in medical consultations - Harres, Annette (Lawrence Erlbaum Associates, 1998)
Tag questions have traditionally been discussed as linguistic strategies used by nonassertive speakers. This article reports the findings of a qualitative study investigating the use of modal and affective tag questions by 3 Australian female general practitioners. Analysis of 29 audiotaped consultations revealed that tag questions were used as both control and involvement strategies. They were found to be employed by doctors for their potential to elicit information from patients, to summarize and confirm information, and to express empathy and provide positive feedback. The implications of these findings are discussed in the light of general patterns of doctor-patient communication as well as more efficient clinical interaction.